Development of Port‐Site Metastases Following Thoracoscopic Resection of a Neuroblastoma. Issue 1 (23rd July 2015) - Pentek, Falk; Schulte, Johannes H.; Schweiger, Bernd; Metzelder, Martin; Schündeln, Michael M.
Abstract : We report a 26‐month‐old female who developed port‐site metastases of a neuroblastoma following minimally invasive thoracoscopic interventions. After diagnosis of an intrathoracic low‐risk neuroblastoma and 6 months of observation, she developed respiratory problems. She subsequently underwent total resection of a locally progressive tumor via thoracoscopy. Six months later, she developed local relapse and subcutaneous metastases within the thoracic wall. These port‐site metastases were most likely iatrogenic. After excision of metastases, the residual tumor responded well to salvage chemotherapy. The patient has remained in remission for over 4 years. Pediatr Blood Cancer © 2015 Wiley Periodicals, Inc.